Menuai dari Pandemi: Penyalahgunaan Protokol Covid-19 - Edison R.L. Tinambunan (Seri Filsafat Teologi, 2021)
The problem that is currently being faced by the world, including Indonesia, is the Covid-19 pandemic. The pandemic, that has hit the world since the end of 2019, has not shown any signs of ending soon. Covid-19 has claimed many victims and caused enormous losses. In Indonesia, the losses are countless. Suffering, both physical and financial, has become a serious common concern. However, in the midst of such a situation, there are still people who use this pandemic as a business field to illegally reap as much profit as possible. The author conducted a literature research on the misuse of the Covid-19 protocol, by taking data from various available media sources, and then formulated a synthesis. The conclusion that can be drawn from this synthesis is that the effectiveness of the law that underlies the implementation of the Covid-19 mitigation protocol has not been running optimally. There are still people who misuse the protocol as an opportunity to enrich themselves amidst people’s suffering.